Investigating Causal Relations between Public Spending and Economic Growth in Europe - Gadea Rivas, Mª Dolores; Bandres Moline, Eduardo (Revista de Economía Mundial, 2019)
The link between economic growth and the size of the public sector has fueled one of the most wide-ranging debates in economic literature and the empirical evidence is far from conclusive. With dierent techniques that encompass both country-to-country causality analysis with VAR models and standard and grouped panels, we study this relationship for a sample of 25 countries from the 1960s to the present. Our contribution is fundamentally methodological, overcoming several pitfalls of the previous literature, namely, endogeneity, dynamic eects and common patterns. The results do not support the fulllment of the Wagner’s Law and a negative eect of public size on economic growth is highlighted.